2016
DOI: 10.1515/cclm-2015-1279
|View full text |Cite
|
Sign up to set email alerts
|

Activity and expression of dipeptidyl peptidase IV on peripheral blood mononuclear cells in patients with early steroid and disease modifying antirheumatic drugs naïve rheumatoid arthritis

Abstract: Our results show that a decrease in DPPIV serum activity, but not CD26 expression, is present in an early stage of rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…This apparent contradictory result may explain the positive correlation of DPP-4 with disease activity observed in our patients with RA. Of note, a recent study involving 50 patients with RA revealed a decrease in DPP-4 serum activity but not in DPP-4/CD26 expression [ 34 ]. In another study involving 27 patients with RA, there was also an elevation in blood plasma DPP-4 but a decrease of DPP-4/CD26 in peripheral blood mononuclear cells after clinical improvement following treatment [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This apparent contradictory result may explain the positive correlation of DPP-4 with disease activity observed in our patients with RA. Of note, a recent study involving 50 patients with RA revealed a decrease in DPP-4 serum activity but not in DPP-4/CD26 expression [ 34 ]. In another study involving 27 patients with RA, there was also an elevation in blood plasma DPP-4 but a decrease of DPP-4/CD26 in peripheral blood mononuclear cells after clinical improvement following treatment [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…CXCL10 was claimed to be the most relevant chemokine biomarker in patients with rheumatoid arthritis, but also large numbers of CD26-expressing cells were found in these patients ( 158 160 ). Remarkably, although rheumatoid arthritis was not associated with altered levels of soluble CD26, the specific activity of the enzyme was reduced, probably because of glycosylation ( 161 , 162 ). In mice, inhibition of CD26 was found to protect CXCL10 from inactivation, resulting in enhanced T cell infiltration into the tumor tissue, thereby improving not only the natural antitumor immunity but also the response to existing immunotherapies ( 156 ).…”
Section: Regulation Of Ifn-inducible Cxcr3 Ligand Activity By Posttramentioning
confidence: 99%
“…type II diabetes and metabolic syndrome) , auto‐immunity (i.e. multiple sclerosis, rheumatoid arthritis) and cancer (i.e. B‐cell leukaemia, hepatocellular carcinoma, bladder cancer) .…”
Section: Discussionmentioning
confidence: 99%